Aplikasi Pengolahan Citra Untuk Identifikasi Produk Berdasarkan Label Kemasannya - Sudjadi, Sudjadi; Somantri, Maman; Yudanto, Scifo Anggi; Prasetyo, Hanung (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
The development of information technology today is growing very fast. The software not only required in running a fast execution but also efficient in the utilization of network bandwidth so that traffic does not become heavy. With the swift network-based computing devices into everyday life, the higher the demand to take advantage of technology agent in the process of problem solving based mobility. This study purpose to implement technology on a mobile Agent software with a case study of a software used to perform a book search on multiple database servers. In software, the agent will move from one database server to another server database to find books that sought out and returned to the client computer and show the results obtained. In this research using Aglet 2.0.2 as the software used for build of such applications. Aglet is used to develop agents who will move from one computer to another computer. To view the search results using PHP and HTML language. Based on the results of tests have been done, the conclusion that application could be implemented by the method of Mobile Agents. Mobile Agents used consists of three kind of AgentOne which serves to make AgentTwo and send it to computer database server, AgentTwo which serves to find the books what are looking for and make AgentThree, and AgentThree which serves to bring the results and go back to the client computer. These three agents formed a collaboration of good programs so the system book search can work as expected. Keywords : Agent, Mobile Agent, Aglets, Book Searching